If not now, when? The timing of childbirth and labour market outcomes - Matteo Picchio; Claudia Pigini; Stefano Staffolani; Alina Verashchagina (Global Labor Organization (GLO), 2018)
We study the effect of childbirth and its timing on female labour market outcomes in Italy. The impact on yearly labour earnings and participation is traced up to 21 years since school completion by estimating a factor analytic model with dynamic selection into treatments. We find that childbearing, especially the first delivery, negatively affects female labour supply. Women having their first child soon after school completion are able to catch up with childless women only after 12–15 years. The timing matters, with minimal negative consequences observed if the first child is delayed up to 7–9 years after exiting formal education.
Keywords: C33; C35; J13; J22; 330; Female labour supply; fertility; discrete choice models; dynamic treatment effect; factor analytic model